ChemInform Abstract: Ionic Liquids as Unique Solvents in One‐Pot Synthesis of 4‐(N, 2, 2, 2‐Tetranitroethylamino)‐3‐R‐furazans. Issue 6 (11th February 2014) - Sheremetev, Aleksei B.; Aleksandrova, Nataly S.; Palysaeva, Nadezhda V.; Struchkova, Marina I.; Tartakovsky, Vladimir A.; Suponitsky, Kyrill Yu.
Abstract The prepared furazanes are thoroughly investigated by NMR spectroscopy and X‐ray crystallography.